2019
DOI: 10.1038/s41598-019-42163-4
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Vacuolating Cytotoxin A Causes Anorexia and Anxiety via Hypothalamic Urocortin 1 in Mice

Abstract: Helicobacter pylori ( Hp ) infection is related to the pathogenesis of chronic gastric disorders and extragastric diseases. Here, we examined the anorexigenic and anxiogenic effects of Hp vacuolating cytotoxin A (VacA) through activation of hypothalamic urocortin1 (Ucn1). VacA was detected in the hypothalamus after peripheral administration and increased Ucn1 mRNA expression and c-Fos-positive cells in the hypothalamus but not in the nucleus tractus soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A few studies have identified some toxic factors released by H. pylori that could pose a threat to the structural integrity of the tight junctions within the blood-brain barrier, potentially causing harm to the central nervous system (CNS). [20,21]. Amongst toxic elements, Vacuolating cytotoxin (VacA toxin), discovered in the hypothalamus after peripheral injection, induces anorexia and anxiety in mice [20].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…A few studies have identified some toxic factors released by H. pylori that could pose a threat to the structural integrity of the tight junctions within the blood-brain barrier, potentially causing harm to the central nervous system (CNS). [20,21]. Amongst toxic elements, Vacuolating cytotoxin (VacA toxin), discovered in the hypothalamus after peripheral injection, induces anorexia and anxiety in mice [20].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Vacuolating cytotoxin A (VacA) is a major cytotoxin produced by Hp in the stomach (Cover et al, 2005). VacA might travels via the peripheral circulation, passes through the bloodbrain barrier (BBB) and affects entire brain including hypothalamus (Suzuki et al, 2019). Helicobacter pylori infection can lead to chronic inflammation (Abadi et al, 2017), and various inflammatory mediators, produced locally in the stomach, such as interleukin (IL) −1β, 6, −8, −10, and −12, tumor necrosis factor (TNF) and interferon (IFN)γ, might reach the circulation and induce neuroinflammation and toxicity (Peek et al, 2010;Alvarez-Arellano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, unexpected results may be produced since H. pylori infection leads to increased expression of IL12 and IFN γ in Mongolian gerbils, which seriously affects the accuracy of experimental results [ 25 27 ]. Besides, H. pylori infection may induce extragastric diseases, making it difficult to determine the health status of experimental gerbils [ 28 ]. Though H. pylori detection before replicating the H. pylori -infected model in gerbils is necessary, we found few studies that used H. pylori -free gerbils or detected the natural infection before challenge with H. pylori [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%